Liquid-liquid phase coexistence and membraneless organelles - Keating, Christine D. (Methods in enzymology, 2021)
Methods in Enzymology, Volume 646, continues the legacy of this premier serial with quality chapters authored by leaders in the field. Chapters in this new release include Methods for Studying RNA condensation/granules in vitro, RNA Dynamics in Intracellular Condensates, Methods for Viscoelastic Characterization of Liquid and Gel Condensates, Incorporating Proteins into Complex Coacervates, Methods for Study of Liquid-Liquid Phase Coexistence in Proximity to Lipid Membranes, Preparation of and Solute Partitioning in Multiphase Coacervates, Reversible photocontrol of DNA coacervation, Enzymatic Control over Coacervation, and much more.